HISTORY OF the HUNTING IN THE CHIEFTAINSHIP OF THE LOGOS-DOKA OF 1903 A 2016 - Marie BOUNDAWANE ,; Edouard DJUMA NGOY,; TASILE ALITRI Joseph, (IJRDO - Journal of Social Science and Humanities Research, 2019)
In olden days ,the space came true of several manners or by the hunters (fighters)which made the search (research) for the abounding in game lands ; if ground is precious for them settle down and directly they become the owners of aforementioned  Space ; our concern was to know the general data about the hunting in the chieftainship of Logo-Doka ,to describe activities of  the hunting in the chieftainship of Logo-Doka in them.          Evolution and to know the attitudes of contemporary Logo-Doka in the face of (in front of) the hunting in the chieftainship, with the historic method and the technique of interview structured  we are accomplished to say that the data on the hunting in the  chieftainship of Logo-Doka ,although there is regression nowadays as titular of example ,Hunting in run(roamed) by place